Bis[4-(chloroacetyl)phenyl] ether - Fan-Lei Meng (Acta Crystallographica Section E, 2008)
The title compound, C16H12Cl2O3, crystallizes with two independent molecules in the asymmetric unit. The dihedral angles between the planes of the benzene rings in the two independent molecules are 68.65 (2) and 68.47 (3)°. The short distance of 3.899 (5) Å between the centroids of the benzene rings of neighbouring molecules indicate π–π interactions. The crystal structure is stabilized by a network of intermolecular C—H...O hydrogen bonds.